Island health: Hope and challenges for public health - Binns, C.; Hokama, T.; Low, W.Y. (SAGE Publications, 2010)
The Asia-Pacific region is a region of small islands, perhaps 100 000 of them. The health, communication, and development problems of islands present difficult challenges for the delivery of health care. The discussions at the Okinawa Symposium centred on how health can be provided to all in the region, not only those in metropolitan areas, but also the poor in rural areas and those on living on far-flung island archipelagos. It is important to apply principles of ``public health'' and ``primary health care'' so that all island residents may have a reasonable expectation of health care. Schools of public health have a special responsibility to educate those who are responsible for the delivery and management of health care in these remote locations. The development of telehealth systems will be important to support health workers in remote locations and to deliver continuing education programs.